Optimizing Energy Solutions for Second Homes: A Study on Energy Efficiency, Cost-effectiveness, and Environmental Impact in the Swedish Context - Yin,Wanli (2024)
This study aims to identify the most cost-effective and environmentally friendly retrofit solutions for enhancing the energy efficiency of second homes in Sweden. Second homes, often used intermittently throughout the year, represent a significant portion of residential energy use and carbon emissions. Therefore, optimizing energy consumption in these homes is critical for achieving national and global climate targets. The study analyzes various retrofit measures and understands how different occupancy patterns, climate conditions, and indoor temperature set points influence energy use, cost-effectiveness, and environmental impact. Four specific retrofit measures were considered: (A) window retrofits by replacing all existing windows with triple-glazed units with a low U-value (0.8 W/m²K), (B) building envelope insulation by adding 100 mm of rock wool to the roof, (C) upgrading to a high-efficiency heating system using Air Source Heat Pump (ASHP) (air-to-air heat pump and air-to-water heat pump) with a Coefficient of Performance (COP) of 3, and (D) installing a solar photovoltaic (PV) system on the roof. These measures were combined into 15 different retrofit scenarios for comparative analysis. Additionally, three scenarios each for occupancy activities (low, medium, and high), climate conditions (southern coast, capital region, and mountainous north), and indoor temperature set points (16°C, 10°C, 5°C during unoccupied periods) were analyzed to evaluate their impacts on energy savings. The research was conducted using a comprehensive approach involving simulation and modeling tools. The energy performance of different retrofit scenarios was simulated using IDA-ICE to estimate the annual energy use and potential savings. A Life Cycle Cost (LCC) analysis was performed to evaluate the cost-effectiveness of each retrofit scenario, following established standards and guidelines for calculating Net Present Value (NPV). The cost analysis accounted for factors such as initial retrofit costs, operation and maintenance (O&M) costs, energy savings, and reinvestment needs over a 25-year project lifetime. The environmental impact of each scenario was assessed through a Life Cycle Assessment (LCA) using Environmental Product Declarations (EPDs) for materials and energy systems. The assessment focused on each retrofit measure's Global Warming Potential (GWP) over its life cycle, considering both embodied carbon and operational energy savings. Key findings revealed that retrofit scenarios involving combinations of high-efficiency heating systems (ASHP), building envelope improvements (roof insulation), and PV systems yielded the highest energy savings, especially under colder climate conditions. The most cost-effective scenarios were those that balanced moderate initial retrofit costs with substantial energy savings, particularly those that included the PV system. The scenarios include a combination of ASHP installation and PV system (CD) showed a significant reduction in energy use and a positive NPV, demonstrating financial viability over the project lifetime. In contrast, the scenario combining building insulation, ASHP with solar PV (BCD) was effective in minimizing greenhouse gas emissions and also had a shorter equivalent compensation year. An eco-efficiency assessment was conducted to provide a holistic view by combining LCC and LCA results into a standardized index. This approach highlighted scenarios where both economic and environmental benefits were optimized. For example, the combination of roof insulation retrofits, ASHP installation, and roof PV system (Scenario BCD) achieved the highest eco-efficiency score, balancing cost savings with significant reductions in CO2 emissions. Sensitivity analyses were performed by varying the weights assigned to cost-effectiveness and environmental impact, revealing that the optimal retrofit solution is highly dependent on the decision-maker's priorities. A scenario with a higher weight for environmental impact favored combinations involving solar PV, whereas a higher weight for cost-effectiveness leaned towards scenarios focusing on building envelope improvements (roof insulation). The findings suggest that selecting the optimal energy retrofit strategy for second homes requires careful consideration of both economic and environmental objectives, as well as contextual factors such as occupancy patterns and climate conditions. The study concludes that while deep energy retrofits can provide significant energy savings and environmental benefits, the choice of specific measures must be tailored to each case to achieve the best balance of cost and sustainability. This research provides a valuable framework and decision-making tool for homeowners, policymakers, and energy consultants aiming to reduce the environmental footprint and operational costs of second homes.
Keywords: Second homes; Retrofit Optimization; Life Cycle Cost (LCC); Environmental Impact; Life Cycle Assessment (LCA); Energy Efficiency